(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2017)
The following lines analyze what we know and we do not know about the study of health inequalities as a field of research in Health Economics from the perspective of the existing public policies. For this purpose, the paper reviews the study of the impact of the crisis on health, the empirical fields of validation, the most determinant variables associated with the economic cycle, their effects on the social capital of countries and their reverse causality of its interrelation with economic growth. It also discusses the main measures of cushioning the crisis in those social determinants which affect health and the variables of intervention in public policies that try to neutralize their consequences minimally. The text concludes with a reflection on those aspects of analysis that complicate to move from diagnosis to prognosis in the implementation of public policies.